WARIS DALAM PRESPEKTIF PEMIKIRAN MUHAMMAD SHAHRUR: SEBUAH PENDEKATAN TEORI HUDUD - Bagus Setiawan; Waldi Nopriansyah; Nova Yanti Maleha (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2023)
Al-Qur'an has determined the amount of inheritance distribution to the heirs. Regarding the issue of inheritance distribution, Shahrur then criticized that inheritance distribution had so far been considered rigid and not in accordance with the demands of social development, especially with regard to the issue of inheritance distribution for women. Therefore, this article discusses inheritance from the perspective of Muhammad Shahrur. This research method is qualitative. The results of the research show that Shahrur criticizes the distribution of inheritance between men and women, which is proportional to 2:1, is not absolute, and can change according to certain conditions. The theory of hudud or limitations is a solution to solving problems regarding inheritance rights. Through his hudud theory, a fair and equitable distribution of inheritance can be realized if the number of men and women is the same, for example; 1 boy + 1 girl, 2 boys + 2 girls, and so on. In addition, Syahrur emphasized the priority of wills over the inheritance. This is because the choice is closer to the value of the principle of justice or equity.